An Investigation of Keratoplasty Procedures and Their Outcomes in Iraq - Leki, Rafid Hameed; Hind Essa Khairan; Meqdam Dawood Salman (Sriwijaya Journal of Ophthalmology, 2024)
Introduction: The treatment of corneal disorders involves the use of various forms of keratoplasty. The objective of this study was to provide a detailed description of the various types of keratoplasty procedures performed in Iraq, as well as their corresponding outcomes. Methods: An observational study was conducted at Al-Zahraa Teaching Hospital to document cases of keratoplasty. The collected data included age, gender, types of keratoplasty, indications, previous surgical or medical history, and postoperative outcomes. The types of keratoplasty included penetrating keratoplasty (PKP), deep anterior lamellar keratoplasty (DALK), and Descemet's stripping endothelial keratoplasty (DSEK). Additionally, we performed cataract surgery and intraocular lens (IOL) insertion for those with cataracts, using either IOLs with scleral fixation or IOLs with iris fixation. We complete the task on the first day following the purchase order, then the first week, the first month, and every six months thereafter. Prior to surgery, patients with corneal vascularization had laser photocoagulation of the blood vessels in the cornea. Results: Ages range from 4 to 90. People over 40 (60.8%) were the most common age group. The female prevalence was 52.9%. Right-eye illness was diagnosed 51.6% of the time. 60% of patients underwent PKP. 26.8% had DALK, 12.4% had DSEK. Post keratoplasty, the statistically-significant improvement-ratio was 68.5% as eyes best corrected visual acuity (BCVA) improvement, while 12.2% of eyes showed a decline in BCVA and 19.3% discharged with no changes in BCVA. Postoperatively, BCVA was significantly lower in cases with a duration below 1 year (1.5), and better among the duration > 3 years (0.5). The greatest improvements were seen in cases with infective keratitis (-0.7), corneal dystrophies (-0.6), and advanced keratoconus (-0.7) whereas the lowest rates were documented in cases with a graft rejection (-0.3), and bullous keratopathy (-0.3) Conclusion: Keratoplasty is associated with a substantial enhancement of visual acuity in the younger population. Infective keratitis, keratoconus, and corneal dystrophy produce the most optimal and superior results. The PKP method is the most frequently performed.